Hidroresfriamento, revestimento comestível e cálcio como alternativas no tratamento pós-colheita de pedúnculos de caju - Sena, Edinaldo de Oliveira Alves (2016)
This study aimed use alternative technologies, physical and chemical, to preserve commercial quality, improve storage capacity and extend the shelf life of cashew apples (Anacardium occidentale L.). To determine the temperature to be used in hydrocooling, peduncles were immersed in water containing ice at 1, 3, 5 and 7°C. Cooling rate, color, freshness, visual evaluation, weight loss and thermal properties were determined. After application of hydrocooling the peduncles were stored for 15 days in a vertical display cooler at 5°C. The hydrocooling temperature which best maintained the quality of peduncles without inducing chilling injury was soffening 5 ° C with 29 min cooling time. After determining the hydrocooling temperature, peduncles cashew apple fresh were hydrocooled or cooled in the cooler at 5°C 25 days peduncles cashew apple. Every five days, for physical, physico-chemical and enzymatic samples were withdrawn analysis. Hydrocooling retarded weight loss, ascorbic acid degradation and acidity, and less of PPO and POD enzyme activity when compared to fruit cooled by air. There were no significant differences carotenoid content, apparent phenols, soluble solids and color between the treatments. Thus, hydrocooling performed as an effective cooling technology and maintained the quality of cashew peduncles. To study the edible coating, peduncles underwent four treatments: hydrocooling, hydrocooling with posterior application of calcium chloride (2%), edible coating based on corn starch (4%), and edible coating enriched calcium. After application of treatments peduncles were stored for 25 days. Every with five days, samples were taken for biochemical, physical, physico-chemical and enzymatic analyzes. Calcium application with both edible coating and after hydrocooling provided greater firmness and less activity of pectinametylesterase and polyphenoloxydase of peduncles, maintaining the integrity of the cell wall. Hydrocooling decreased weight loss and degradadation of anthocyanins and carotenoids, which resulted in the maintenance of visual quality, and less degradation of ascorbic acid. The maize starch based coating was not effective in maintaining the quality of peduncles during the storage period. Cashew apples, when hydrocooled retained acce quality for over 20 days; the other treatments shelf life ranged from 15 to 20 days. These results suggest that the use of hydrocooling and utilization of calcium were effective in preserving the quality and shelf life of cashew peduncles.